2015
DOI: 10.1016/j.atmosenv.2015.04.056
|View full text |Cite
|
Sign up to set email alerts
|

A study of global atmospheric budget and distribution of acetone using global atmospheric model STOCHEM-CRI

Abstract: h i g h l i g h t sPhotochemical production from monoterpenes gives 64% to the global acetone sources. The tropospheric life-time of acetone is found to be 18 days. Higher acetone is found over the forested regions throughout the summer. Good agreement between model and measurement data for acetone is found. a b s t r a c tThe impact of including a more detailed VOC oxidation scheme (CRI v2-R5) with a multi-generational approach for simulating tropospheric acetone is investigated using a 3-D global model, STOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 55 publications
(106 reference statements)
4
69
1
2
Order By: Relevance
“…We used an ‰; this change is insignificant relative to our measurement errors and can therefore be ignored (Table S2, Methane and non-methane hydrocarbon (NMHC) oxidation accounts for approximately half of the global CO budget (Duncan et al, 2007) and we estimate the contribution of these to the wintertime Indianapolis urban CO budget. Compounds such as OH and O 3 readily oxidize CH 4 and many NMHCs (Sander et al, 2006; Warneke et al, 2013;Russo et al, 2011;Khan et al, 2015) making them seasonally-varying sources of CO (Duncan et al, 2007). However, the relatively low wintertime NMHC and OH mole fractions (Helmig et al, 2013; Hu et al, 2015) mean that CH 4 and NMHC oxidation may be unimportant for our study.…”
Section: Simplification Of the Indianapolis Winter Co Budgetmentioning
confidence: 59%
See 1 more Smart Citation
“…We used an ‰; this change is insignificant relative to our measurement errors and can therefore be ignored (Table S2, Methane and non-methane hydrocarbon (NMHC) oxidation accounts for approximately half of the global CO budget (Duncan et al, 2007) and we estimate the contribution of these to the wintertime Indianapolis urban CO budget. Compounds such as OH and O 3 readily oxidize CH 4 and many NMHCs (Sander et al, 2006; Warneke et al, 2013;Russo et al, 2011;Khan et al, 2015) making them seasonally-varying sources of CO (Duncan et al, 2007). However, the relatively low wintertime NMHC and OH mole fractions (Helmig et al, 2013; Hu et al, 2015) mean that CH 4 and NMHC oxidation may be unimportant for our study.…”
Section: Simplification Of the Indianapolis Winter Co Budgetmentioning
confidence: 59%
“…However, the relatively low wintertime NMHC and OH mole fractions (Helmig et al, 2013; Hu et al, 2015) mean that CH 4 and NMHC oxidation may be unimportant for our study. Not all NMHC species capable of impacting CO are measured at INX; therefore some of the NMHC mole fractions are estimated using other urban studies in the literature (Warneke et al, 2013;Russo et al, 2011;Khan et al, 2015) (Table S2, supplemental material). Reaction rates with OH were calculated using k OH from Warneke et al (2013) if available, and if not, k OH was calculated using parameters from Sander et al (2006), and Atkinson et al, (1999, 2006.…”
mentioning
confidence: 99%
“…These results are in line with the previous evaluation of Pozzer et al (2007, Table 8), who observed an underestimation of ∼ 50-35 % for the same biogenic emissions as used here (55 Tg a −1 ), which account for ∼ 85 % of the total emissions. These results indicate the need for considering oceanic emissions and photochemical production of CH 3 COCH 3 from monoterpenes, methylbutenol, and higher iso-alkanes Khan et al, 2015), which were not included. For example Pozzer et al (2010) showed that i-butane and i-pentane are responsible for the photochemical production of 4.3 and 5.8 Tg a −1 of CH 3 COCH 3 , respectively.…”
Section: Chemistry In the Upper Troposphere And Lower Stratosphere (Umentioning
confidence: 99%
“…Depending on the season and geographical location the ocean can either be a sink (82 Tg yr −1 ) or a source (80 Tg yr −1 ) of acetone . Khan et al (2015), on the other hand, calculate a global acetone source of 72.7 Tg yr −1 , of which 55.6 Tg yr −1 are photochemical production from α-pinene, β-pinene and propane and 17.1 Tg yr −1 direct emission. From the total sink of 72.9 Tg yr −1 , 30.8 Tg yr −1 represent OH oxidation, 30.3 Tg yr −1 photolysis and 11.8 Tg yr −1 dry deposition and the ocean is regarded as being globally in a near-equilibrium state (Khan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%